2020
DOI: 10.3354/aei00378
|View full text |Cite
|
Sign up to set email alerts
|

European lobsters utilise Atlantic salmon wastes in coastal integrated multi-trophic aquaculture systems

Abstract: In this study, we investigated if juvenile European lobsters Homarus gammarus would eat waste from Atlantic salmon Salmo salar cages in a coastal integrated multi-trophic aquaculture (IMTA) setup and if there were any impacts on growth. Trophic interactions between salmon and lobsters were assessed using δ15N and δ13C stable isotope analysis and fatty acid profiling from fish feed as indicators of nutrient flow. Analysis revealed that lobsters directly utilised particulate waste from salmon production, as leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 57 publications
(65 reference statements)
0
6
1
Order By: Relevance
“…Essential minerals, such as calcium, may be assimilated when crabs ingest fragments of shells when they feed on natural prey items; low levels of minerals in salmonid feed may lead to deficiencies. Our results contrast with those of previous studies based in the field, where somatic condition of fish and invertebrates frequenting finfish farms was improved when compared to reference areas (Fernandez-Jover et al, 2007;Fernandez-Jover et al, 2011;Dempster et al, 2011;Izquierdo-Gomez et al, 2015), and invertebrate condition and/or growth was unaffected or positively affected by salmon farm wastes in trials pertaining to integrated multi-trophic aquaculture (Sarà et al, 2009;Lander et al, 2012;Baltadakis et al, 2020); only two studies found negative impacts on some variables measured in mussels (Handå et al, 2012;Irisarri et al, 2015).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Essential minerals, such as calcium, may be assimilated when crabs ingest fragments of shells when they feed on natural prey items; low levels of minerals in salmonid feed may lead to deficiencies. Our results contrast with those of previous studies based in the field, where somatic condition of fish and invertebrates frequenting finfish farms was improved when compared to reference areas (Fernandez-Jover et al, 2007;Fernandez-Jover et al, 2011;Dempster et al, 2011;Izquierdo-Gomez et al, 2015), and invertebrate condition and/or growth was unaffected or positively affected by salmon farm wastes in trials pertaining to integrated multi-trophic aquaculture (Sarà et al, 2009;Lander et al, 2012;Baltadakis et al, 2020); only two studies found negative impacts on some variables measured in mussels (Handå et al, 2012;Irisarri et al, 2015).…”
Section: Discussioncontrasting
confidence: 99%
“…In both cases, several species of mobile predators and scavengers tend to be more abundant under farms compared to surrounding areas (Drouin et al, 2015;Callier et al, 2018;Barrett et al, 2019;Theuerkauf et al, 2021). Several taxa have been determined to assimilate energy coming from farms, either directly or indirectly; these include sponges (Laroche et al, 2021), polychaetes (Salvo et al, 2015;White et al, 2017a;Woodcock et al, 2019), echinoderms (White et al, 2017b;Woodcock et al, 2018), bivalves (Handå et al, 2012;Irisarri et al, 2015), and decapods (Olsen et al, 2012;Izquierdo-Gomez et al, 2015;Woodcock et al, 2018;Sardenne et al, 2019;Baltadakis et al, 2020;Sardenne et al, 2020). Therefore, these anthropogenic inputs of resources might impact natural population dynamics, including the productivity of several commercially-important species.…”
Section: Introductionmentioning
confidence: 99%
“…This can be illustrated by a recent study where common juvenile European lobsters (H. gammarus) were held for 319 days close to salmon sea cages. 169 The study showed that the lobsters utilised the salmon waste residues as a food source through stable isotope analysis; however, growth performance was not improved or decreased by this farming strategy. The co-culture dependency would add to the production time scale to achieve the optimal harvest weight of lobsters and would likely be challenging in practice, e.g., disease outbreaks and treatments on the salmon and changing water temperatures.…”
Section: Creating a Sustainable Lobster Farming Modelmentioning
confidence: 96%
“…This is economically beneficial as the cost of feeding is reduced and lessens the environmental impact by transforming waste residues into a valuable co‐product. This can be illustrated by a recent study where common juvenile European lobsters ( H. gammarus ) were held for 319 days close to salmon sea cages 169 . The study showed that the lobsters utilised the salmon waste residues as a food source through stable isotope analysis; however, growth performance was not improved or decreased by this farming strategy.…”
Section: Creating a Sustainable Lobster Farming Modelmentioning
confidence: 99%
“…The combination of different analytical techniques such as fatty acid analysis and SIA has been useful to produce synergic tracers for the accurate determination of trophic transfers between species co-cultivated in IMTA arrays. For example, Baltadakis et al 101 applied isotopic and fatty acid analysis to demonstrate that lobsters (Homarus gammarus) are able to utilize particulated waste derived from salmon cages in a coastal IMTA system. In another study, Sanz-Lazaro and Sanchez-Jerez 104 demonstrated that mussels (Mytilus galloprovincialis) did not assimilate fish farming wastes directly.…”
Section: The Us Efulne Ss Of S Ia To E Xplore N Utrient Dynami C S In Integ R Ated Multi -Trophic Aquaculturementioning
confidence: 99%